2016
DOI: 10.1016/s0924-977x(16)31702-3
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol presents an inverted U-shaped dose-response curve in the simulated public speaking test

Abstract: Objective: Cannabidiol (CBD), one of the non-psychotomimetic compounds of Cannabis sativa, causes anxiolytic-like effects in animals, with typical bell-shaped dose-response curves. No study, however, has investigated whether increasing doses of this drug would also cause similar curves in humans. The objective of this study was to compare the acute effects of different doses of CBD and placebo in healthy volunteers performing a simulated public speaking test (SPST), a well-tested anxiety-inducing method. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
78
0
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(88 citation statements)
references
References 37 publications
4
78
0
6
Order By: Relevance
“…Unfortunately, these studies have very small sample sizes. [36][37][38][39][40][41][42][43][44][45][46][47][48] This means exaggerated responses or lack of significant effects could be due to a lack of statistical power. All of the studies use singledose CBD, so the chronic impact of the drug cannot be determined.…”
Section: Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, these studies have very small sample sizes. [36][37][38][39][40][41][42][43][44][45][46][47][48] This means exaggerated responses or lack of significant effects could be due to a lack of statistical power. All of the studies use singledose CBD, so the chronic impact of the drug cannot be determined.…”
Section: Anxietymentioning
confidence: 99%
“…Responses from normal volunteers to a stressor might be less severe than people with anxiety disorders, diminishing the extent of benefit that could result from effective treatment. [36][37][38][39][40][41][42][43][44][45][46][47][48] The first category of studies assessed the impact of single-dose CBD to attenuate the anxiety-promoting effects of single-dose delta-9-THC. [36][37][38][39] These trials suggest that CBD reduces higher-dose delta-9-THCinduced anxiety as assessed by subjective ratings or the validated Visual Analog Mood Scale or State-Trait Anxiety Inventory.…”
Section: Anxietymentioning
confidence: 99%
See 1 more Smart Citation
“…These studies involved the acute administration of CBD doses, ranging from 100 to 900 mg, which were presumably of a similar order of magnitude to the doses given in the clinical trials mentioned in the previous section for epilepsy, although it is not possible to know for certain as the reported doses were absolute and not given relative to the bodyweight of the subjects. CBD was given 1.5-3.5 hours prior to the public speaking test and was compared with a placebo (Bergamaschi et al 2011;Zuardi et al 2017;Linares et al 2019). Participants in all three studies reported lower levels of anxiety, assessed subjectively by a visual analogue mood scale, when given CBD at doses of either 300 mg (Zuardi et al 2017;Linares et al 2019) or 600 mg (Bergamaschi et al 2011), relative to those who had received placebo.…”
Section: Anxietymentioning
confidence: 99%
“…CBD was given 1.5-3.5 hours prior to the public speaking test and was compared with a placebo (Bergamaschi et al 2011;Zuardi et al 2017;Linares et al 2019). Participants in all three studies reported lower levels of anxiety, assessed subjectively by a visual analogue mood scale, when given CBD at doses of either 300 mg (Zuardi et al 2017;Linares et al 2019) or 600 mg (Bergamaschi et al 2011), relative to those who had received placebo. However, these studies involved a limited number of subjects (n < 60 in total), included both healthy controls and individuals with social anxiety disorder, the range of CBD doses tested varied across the studies, and preparations were provided by different companies.…”
Section: Anxietymentioning
confidence: 99%